Evaluation of Biofertilizers and Parthenium Vemicompost on Tomato Crop - D. R. Chamle2, U. P. Mogle1* and (Journal of Ecobiotechnology, 2011)
Aim of the present investigation was to assess the efficiency of biofertilizers and Parthenium vermicompost on yield of tomato (Lycopersicon esculantum L.). A field experiment was conducted at Jalna Education Society’s Arts, Commerce and Science College, Jalna with 13 treatments and 3 replications. The biofertilizers were used either independently or in amalgamation as compared to recommended fertilizers and reference control. The analysis of the crop was done at 90 days after sowing (DAS). On the basis of the results obtained, it is concluded that the application of bacterial inoculants along with vermicompost (Vc) were more effective in increasing leaf area, total chlorophyll and yield of tomato.